101 FACTORS ASSOCIATED WITH FEAR OF FALLING IN OLDER IRISH ADULTS. (18th November 2021) - Brennan, F; Laird, E; Hughes, C; McNulty, H; Ward, M; Strain, J J; Molloy, A M; Cunningham, C; McCarroll, K
Abstract: Background: Fear of falling is common in older adults and is associated with social isolation, reduced quality of life, depression and increased mortality. We aimed to investigate the factors associated with fear of falling in a cohort of older Irish adults. Methods: Our study included adults aged ≥60 years attending outpatient services and recruited as part of the TUDA (Trinity, Ulster and Department of Agriculture) study. Physical frailty was measured with the Timed Up and Go (TUG), cognition with the Mini Mental State Examination (MMSE) and depression with the Center for Epidemiological Studies Depression scale (CES-D). Factors associated with fear of falling were explored in multinomial regression models. Results: 5185 adults were included, 67.3% female and mean age 74.0 ± 8.3 yrs. Fear of falling varied by age: 39.4% (60-70 yrs), 51.2% (70-80 yrs), 70.4% (80 + yrs). Independent positive predictors of fear of falling were age (beta 0.01, P = 0.030), female gender (OR 2.6, CI 2.2–3.2, P < 0.001), fall in the previous year (OR 1.9, CI 1.6–2.3, P < 0.001), depression (CES-D ≥ 16) (OR 1.7, CI 1.3–2.2, P < 0.001), use of osteoporosis medications (OR 1.3, CI 1.1–1.6, P = 0.002), self reported dizziness on standing (OR 1.5, CI 1.3–1.8, P < 0.001), physical frailty (TUG >12 seconds, OR 1.30, CI 1.1–1.6, P = 0.004) and limiting outside activities (OR 16.3, CI 13.8–19.3, P < 0.001). Conclusion: We identified a high prevalence of fear of falling, though our study sample included frail older adults attending geriatric outpatient services. Those who fell in the last year and who were female were about twice as likely to fear falling. It was also more likely in those who were physically frailer, taking osteoporosis medications and reporting orthostatic symptoms. Notably those with a fear of falling were 70% more likely to be depressed and 16 times more likely to limit outside activities highlighting its negative impact.